National Identity and Welfare Nationalism: Migration, Citizenship, and Social Policy - Cerev, Gökçe; Sarıipek, Doğa Başar (Social Welfare: Interdisciplinary Approach, 2024)
The future course of the welfare state in the context of global capitalism’s expansion is a subject of intense academic debate, with significant scrutiny focused on its trajectory amid globalization. This discourse encompasses inquiries into the economic prerequisites for and ramifications of the welfare state, as well as its alignment with economic competitiveness and political legitimacy. Particularly prominent is the issue of political legitimacy, focusing on the welfare state’s ability to foster social cohesion and ensure democratic governance, given challenges posed by immigration, anti-immigration sentiments, and evolving social risks. These challenges have highlighted a dichotomy within Western European societies, emphasizing distinctions between natives and immigrants based on their positioning within the labor market. Despite migrants’ potential contributions, their reception and integration into destination countries’ social fabric are often hindered by welfare nationalism and concerns regarding declining welfare standards. This nationalism manifests in welfare exclusionism and chauvinism, fueling calls to restrict migrant benefits. Conversely, welfare state ideologies rooted in egalitarian principles serve as a counterbalance to exclusionary demands, shaping debates on migrants’ entitlement to welfare benefits. Against this backdrop, this study aims to elucidate the intricate interplay between pragmatic and nationalist/exclusionary perspectives within the discourse of welfare nationalism. It seeks to achieve this by examining the nexus between welfare rights, national identity formation, the welfare state crisis, and migrants’ positioning within the labor market. Through enriching this debate, the study endeavors to contribute to a deeper understanding of the future trajectory of welfare states characterized by significant migrant populations.